“Energy Communities” and the promotion of resilient societies in the Recovery and Resilience Facility of the European Union - Esteves, A. (EU Green Recovery in the post Covid 19 Period, 2021)
"Energy Communities" Include energy prosumer cooperatives (Wierling et al., 2018), citizen-led municipal energy management systems and other community-led initiatives (CLIs) based on upscaling of production and consumption of renewable energy sources (Wierling et al., 2020; Wierling et al., 2021). Complement the logics of bureaucratization and commodification that respectively mark state-led and market-led approaches, leading to creation of new hybrid institutions, flexibly able to reconcile impulses towards transformation and stability (Wittmayer et al., 2021). Provide not only additional and potentially improved pathways for achieving carbon neutrality and delivery of the SDGs. Regenerative Approach to Post-carbon Transition Treats natural and human processes as inherently linked. Go beyond sustainability to embrace social-ecological resilience, understood as the capacity to adapt, transform, remain cohesive and thrive in face of external pressures. Seeks to arrest and reverse both ecological degradation and loss of the cultural skills necessary for living in harmony with local environments, allowing people to form synergistic interrelationships with each other and with nature.